Evaluation of Income Tax Incentives (PPh) Article 21 In the Midst of The Covid 19 Outbreak at PT Sanipak Indonesia - Aqilla Tasya Damaya (Social Sciences Insights Journal, 2023)
The government made regulations regarding income tax incentives for income tax article 21 as outlined in PMK No.110/PMK.03/2020, this is the impact of covid 19. COVID (Coronavirus Disease) 19 is a virus that causes respiratory infections in humans from the common cold to serious illnesses. Since the Covid-19 outbreak found in Wuhan, China in 2019 has affected the economy of the entire world, including Indonesia. Therefore, the government made a new regulation regarding income tax incentives for article 21 income tax. The author conducted research using a descriptive method so that the results obtained were data on PT Sanipak Indonesia employees who received article 21 income tax incentives and data on PT Sanipak Indonesia employees who did not receive article 21 income tax incentives. A total of 445 employees who did not receive article 21 income tax incentives. Employees who do not receive income tax incentives article 21 are mostly because they do not have an NPWP.